2014
DOI: 10.1093/mnras/stu467
|View full text |Cite
|
Sign up to set email alerts
|

Deep radio observations of the radio halo of the bullet cluster 1E 0657-55.8

Abstract: We present deep 1.1-3.1 GHz Australia Telescope Compact Array observations of the radio halo of the bullet cluster, 1E 0657−55.8. In comparison to existing images of this radio halo, the detection in our images is at higher significance. The radio halo is as extended as the X-ray emission in the direction of cluster merger but is significantly less extended than the X-ray emission in the perpendicular direction. At low significance, we detect a faint second peak in the radio halo close to the X-ray centroid of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
174
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(205 citation statements)
references
References 46 publications
(79 reference statements)
26
174
5
Order By: Relevance
“…A similar situation is observed in the Bullet cluster (Shimwell et al 2014) and in Abell520 Markevitch 2010;Vacca et al 2014), the Coma Cluster (Planck Collaboration et al 2013; Uchida et al 2015), and Abell754 (Macario et al 2011). Therefore, this seems to be a common phenomenon.…”
Section: Radio Halo Relic Shocks and Turbulence Connectionsupporting
confidence: 62%
“…A similar situation is observed in the Bullet cluster (Shimwell et al 2014) and in Abell520 Markevitch 2010;Vacca et al 2014), the Coma Cluster (Planck Collaboration et al 2013; Uchida et al 2015), and Abell754 (Macario et al 2011). Therefore, this seems to be a common phenomenon.…”
Section: Radio Halo Relic Shocks and Turbulence Connectionsupporting
confidence: 62%
“…The halo in MACS J0416.1-2403 is also rather elongated compared to most known radio halos. However, there are other clusters with similarly elongated radio halos (e.g., Bonafede et al 2012;van Weeren et al 2012avan Weeren et al , 2012bShimwell et al 2014). …”
Section: A Newly Discovered Radio Halomentioning
confidence: 99%
“…A textbook example of a merging cluster with a bright radio halo is the famous Bullet cluster, 1E 0657-56 (Elvis et al 1992;Liang et al 2000;Markevitch et al 2002;Shimwell et al 2014). Chandra has revealed that this system has a bullet-like subcluster core moving through the disturbed ICM of the main cluster (Markevitch et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The spectral index map of the radio emission appears not to be smooth, with regions N and W of the core steeper than the S (localised variations in the spectral index of the Bullet Cluster were also observed by Shimwell et al 2014). This may indicate that the halo is still forming and the diffuse radio emission is being varied locally by the proximity to shocks and the amount of turbulence.…”
Section: Nw and Se X-ray Shock Frontsmentioning
confidence: 99%